The Effect Of Bisphosphonate Risedronate Emulgel On The Inhibition Of Relaps Tooth Movement - Utari, Tita Ratya; Mirnacantika, Bellinda Aprillia; Zulfikar, Trinadya Muhammad; Syadzanisa, Farah Fauzia; Wulandari, Ika Sukma (Odonto : Dental Journal, 2023)
Background: Orthodontic treatment is performed to correct the malocclusion, and after treatment is complete. The position of the teeth must be maintained because the teeth can move back to their original position, commonly known as relapse. Various attempts have been made, such as using retainers, and various studies have used pharmacological agents such as bisphosphonate risedronate to inhibit relapse, but these studies still used the injection method, which is inconvenient to apply and has a systemic effect. For this reason, changing the bisphosphonate preparation to an emulgel will facilitate its application and have a local effect, but it is necessary to test and determine its effectiveness in inhibiting the relapse. Method: An experimental laboratory study was conducted on 18 guinea pigs, which were divided into three groups: I (control), II (emulgel without risedronate), and III (emulgel with risedronate). The teeth were moved with open coil springs on both lower incisors for seven days, stabilized for seven days, and emulgel applied in groups II and III. The coil spring was removed, and the distance between the two incisors was measured on the third and seventh days. Result: Using One-Way ANOVA and Post Hoc LSD, the data analysis results showed significant differences between the control and the risedronate emulgel groups on the third and seventh days. The largest relapse occurred in the control group, while the smallest was in the emulgel group with risedronate. Conclusion: These results indicate that risedronate bisphosphonate in the form of emulgel influences inhibiting the movement of tooth relapse